Cost-effectiveness of different caries preventive measures in a high-risk population of Swedish adolescents - Oscarson N, Ka¨llesta° l C, Fjelddahl A, Lindholm L. (Blackwell Synergy, 2003)
A total of 3373 12-year-olds agreed to participate in an intervention study evaluating different caries preventive measures. The study, titled ‘Evaluation of caries preventive measures’, was performed between 1995 and 1999 at 26 dental health clinics throughout Sweden. At the start of the study, the subjects were classified as individuals at high or low risk of developing caries.